Freshwater salinization of seasonal ponds: high salinity and stratification threaten critical, overlooked habitats - Brady, Steven; Benoit, Gaboury (Environmental Science & Technology, 2025)
Keywords: Biology; Critical habitat; Ecology; Environmental science; Fishery; Geology; Habitat; Oceanography; Salinity; Soil salinity; Stratification (seeds); dept; bio; peer-reviewed

A continuum of genetic mixing for conservation management along the (mal)adaptation spectrum: A comment on Hoffmann et al. - Crispo, Erika; Derry, Alison M.; Brady, Steven P. (Evolutionary Applications, 2021)
When restoring gene flow for conservation management, genetic variation should be viewed along a continuum of genetic divergence between donor and recipient populations. On the one hand, maintaining local adaptation (low divergence between donors and recipients) can enhance conservation success in the short term. On the other hand, reducing local adaptation in the short term by increasing genetic diversity (high divergence between some donors and recipients) might have better long-term success in the face of changing environmental conditions. Both Hoffman et al. (2020) and a paper we previously published in a Special Issue on Maladaptation in Applied Conservation (Derry et al., 2019) provide frameworks and syntheses for how best to apply conservation strategies in light of genetic variation and adaptation. A key difference between these two studies was that whereas Derry et al. (2019) performed a quantitative meta-analysis, Hoffman et al. (2020) relied on case studies and theoretical considerations, yielding slightly different conclusions. We here provide a summary of the two studies and contrast of the main similarities and differences between them, while highlighting terminology used to describe and explain main concepts. © 2021 The Authors. Evolutionary Applications published by John Wiley & Sons Ltd
0 citations (Crossref) [2023-10-31] Type: Note tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85099868646
Keywords: dept.bio; peer-reviewed

Freshwater salinization leads to sluggish, bloated frogs and small, cramped embryos but adaptive countergradient variation in eggs - Brady, Steven; Kang, Samantha; Wang, Z.; Layne, Craig; Calsbeek, Ryan (Integrative and Comparative Biology, 2025)
Keywords: Amphibian; Aquatic ecosystem; Biology; Cottus; Ecology; Ecosystem; Freshwater ecosystem; Habitat; Population; Salinity; Soil salinity; dept.bio

Road salt compromises functional morphology of larval gills in populations of an amphibian. - Szeligowski, Richard V.; Scanley, Jules A.; Broadbridge, Christine C.; Brady, Steven P. (Environmental pollution (Barking, Essex : 1987), 2021)
Across the planet, winter de-icing practices have caused secondary salinization of freshwater habitats. Many amphibians are vulnerable because of permeable skin and reliance on small ponds, where salinity can be high. Early developmental stages of amphibians are especially sensitive to salt, and larvae developing in salt-polluted environments must osmoregulate through ion exchange in gills. Though ionoregulation in amphibian gills is generally understood, the role of gill morphology remains poorly described. Yet gill structure should affect ionoregulatory capacity, for instance in terms of available surface area. As larval amphibian gills also play critical roles in gas exchange and foraging, changes in gill morphology from salt pollution potentially affect not only osmoregulation, but also respiration and feeding. Here, we used an exposure experiment to quantify salinity effects on larval gill morphology in wood frogs (Rana sylvatica). We measured a suite of morphological traits on gill tufts—where ionoregulation and gas exchange occur—and on gill filters used in feeding. Larvae raised in elevated salinity developed larger gill tufts but with lower surface area to volume ratio. Epithelial cells on these tufts were less circular but occurred at higher densities. Gill filters showed increased spacing, likely reducing feeding efficiency. Many morphological gill traits responded quadratically, suggesting that salinity might induce plasticity in gills at intermediate concentrations until energetic demands exceed plasticity. Together, these changes likely diminish ionoregulatory and respiratory functionality of gill tufts, and compromise feeding functionality of gill filters. Thus, a singular change in aquatic environment from a widespread pollutant appears to generate a suite of consequences via changes in gill morphology. Critically, these changes in traits likely compound the severity of fitness impacts in populations dwelling in salinized environments, whereby ionoregulatory energetic demands should increase respiratory and foraging demands, but in individuals who possess structures poorly adapted for these functions. © 2021 Elsevier Ltd
2 citations (Crossref) [2023-10-31]
Keywords: Amphibia; Animals; Article; Feeding; Freshwater habitats; Functional morphology; Gas exchange; Gill morphology; Gills; Humans; Ion exchange; Larva; Morphology; Osmoregulation; Osmosis; Osmotic stress; Plasticity; Pollution; Rana sylvatica; Ranidae; Road effect; Road salts; Roads and streets; Salinisation; Secondary salinization; Sodium Chloride; Surface area; amphibian; animal; animal cell; animal experiment; animal tissue; aquatic environment; breathing; cell density; cell structure; controlled study; dept.bio; developmental stage; embryo; energetic demand; energy; epithelium cell; exposure; foraging; functional morphology; gill; gill filter; gill length; gill tuft; human; larva; length; nonhuman; osmoregulation; peer-reviewed; plasticity; pollution exposure; road; salinity; salinization; salt; sodium chloride; surface area; volume

Alternative splicing and parallel patterns of gene expression underlie population and life history divergence in an amphibian - Hu, Juntao; Ren, Xingyue; Barrett, Rowan; Samma, Eman; Sulkowski, Mikloaj; Brady, Steven (2025)
Keywords: Alternative splicing; Amphibian; Biology; Computational biology; Demography; Divergence (linguistics); Ecology; Evolutionary biology; Gene; Gene expression; Genetics; Life history; Messenger RNA; Population; RNA splicing; Sociology; dept.bio

Alternative Splicing and Gene Expression Variation Underlie Population and Life History Differences in an Amphibian - Hu, Juntao; Ren, Xingyue; Barrett, Rowan; Samma, Eman; Sulkowski, Mikolaj; Brady, Steven (Ecology and Evolution, 2025)
ABSTRACT Phenotypic variation is common across life history and among populations occupying different environments, yet the molecular mechanisms underlying these axes of divergence remain poorly understood. Much work has focused on gene expression as a link between genetic variation, environmental variation, and phenotypes, but post‐transcriptional processes such as alternative splicing—which affect how transcripts are assembled rather than how much of a transcript is produced—are increasingly recognized as additional modulators of plasticity and adaptation. Here, we examined gene expression and alternative splicing together in the wood frog ( Rana sylvatica ), an amphibian with a complex life cycle whose populations differ across replicated gradients of road adjacency and associated pollution. We found extensive transcriptomic differences between hatchlings and adults, with thousands of genes differentially expressed or spliced. Individuals clustered strongly by population for both expression and splicing. Differences at the habitat level were less extensive, but revealed two differentially expressed genes ( HSP70 and Gpsm2 ) and one differentially spliced gene ( Cd82 ) that consistently distinguished roadside and woodland populations. Overall, genetic differentiation between populations was low, suggesting that phenotypic and transcriptomic differences likely emerge in the presence of gene flow and reflect plastic responses. Together, these results highlight transcriptomic plasticity as an important mechanism shaping variation across both development and population differentiation.
Keywords: Alternative splicing; Amphibian; Gene; Gene expression; Genetic variation; Phenotypic plasticity; Population; Transcriptome; alternative splicing; dept.bio; gene expression; local adaptation; maladaptation; population divergence

Edema as a solute sink: lymphatic sequestration may buffer plasma ion balance under freshwater salinization in the wood frog (Rana sylvatica) - Jaansalu, Matthew; Jones, Olivia; Kutschinski, Matilda; Arounsack-Colon, Santi; Kelsey, Oliver; Wang, Z.; Bond, Megan; Layne, Craig; Brady, Steven (SSRN Electronic Journal, 2026)
Keywords: Body water; Chloride; Edema; Lymphatic system; Redistribution (election); Salinity; Swelling; Tissue fluid; dept.bio

Population Origin and Heritable Effects Mediate Road Salt Toxicity and Thermal Stress - Conner, Lauren M.; Goedert, Debora; Fitzpatrick, Sarah W.; Fearnley, Amber; Gallagher, Emma L.; Peterman, Jessica D.; Forgione, Mia E.; Kokosinska, Sophia; Hamilton, Malik; Masala, Lydia A.; Merola, Neil; Rico, Hennesy; et al. (2023)
Human impacts on wild populations are numerous and extensive, degrading habitats and causing population declines across taxa. Though these impacts are often studied individually, wild populations typically face suites of stressors acting concomitantly, compromising the fitness of individuals and populations in ways poorly understood and not easily predicted by the effects of any single stressor. Developing understanding of the effects of multiple stressors and their potential interactions remains a critical challenge in environmental biology. Here, we focus on assessing the impacts of two prominent stressors affecting many organisms across the planet – elevated salinity (an increasingly common pollutant in freshwater habitats) and elevated temperature. We examined a suite of physiological traits and components of fitness across populations of wood frogs originating from ponds that differ in their proximity to roads and thus their legacy of exposure to road salt pollution. When experimentally exposed to road salt, wood frogs showed reduced survival, especially those from ponds adjacent to roads, and delayed time to metamorphosis. Family level effects mediated these outcomes, but high salinity generally eroded family level variance. When combined, exposure to both temperature and salt resulted in very low survival, and this effect was strongest in roadside populations. Taken together, these results suggest that temperature is an important stressor capable of exacerbating impacts from a prominent contaminant confronting many freshwater organisms in salinized habitats. More broadly, it appears likely that toxicity might often be underestimated in the absence of multi-stressor approaches.
Keywords: Climate change; Maladaptation; SCSU-student; amphibians; dept.bio; local adaptation; pollution; road salt